Beyond dyadic interdependence: Actor-oriented models for co-evolving social networks and individual behaviors - Burk, W; Steglich, C; Snijders, T (2007)
Actor-oriented models are described as a longitudinal strategy for examining the co-evolution of social networks and individual behaviors. We argue that these models provide advantages over conventional approaches due to their ability to account for inherent dependencies between individuals embedded in a social network (i.e., reciprocity, transitivity) and model interdependencies between network and behavioral dynamics. We provide a brief explanation of actor-oriented processes, followed by a description of parameter estimates, model specification, and selection procedures used by the Simulation Investigation for Empirical Network Analyses (SIENA) software program (Snijders, Steglich, Schweinberger, and Huisman, 2006). To illustrate the applicability of these models, we provide an empirical example investigating the co-evolution of friendship networks and delinquent behaviors in a longitudinal sample of Swedish adolescents with the goal of simultaneously assessing selection and influence processes. Findings suggest both processes play a substantive role in the observed dynamics of delinquent behaviors, with influence having a relatively stronger role than selection (especially in reciprocated friendships).